2020
DOI: 10.3390/nano10050820
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Salvia officinalis L. and Thymus serpyllum L. Extracts Free and Embedded into Mesopores of Silica and Titania Nanomaterials

Abstract: This study evidenced the nanoconfinement effect on polyphenolic extracts prepared from Salvia officinalis L. and Thymus serpyllum L. into the mesopores of silica and titania nanomaterials on their radical scavenging capacity and antimicrobial potential. The ethanolic and hydroalcoholic extracts obtained either by conventional or microwave-assisted extraction were characterized in terms of total polyphenols, total flavonoids, and chlorophyll content, as well as radical scavenging activity by consecrated spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 45 publications
11
28
3
Order By: Relevance
“…In another recent study performed by Brezoiu et al, a moderate improvement in antimicrobial activity was also observed for a polyphenolic extract of Salvia officinalis L. when embedded into the mesopores of a silica-type support compared to the free extract [19].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In another recent study performed by Brezoiu et al, a moderate improvement in antimicrobial activity was also observed for a polyphenolic extract of Salvia officinalis L. when embedded into the mesopores of a silica-type support compared to the free extract [19].…”
Section: Discussionmentioning
confidence: 74%
“…However, regarding the employment of MSNs for embedding polyphenolic extracts, there are only a few reports [ 17 , 18 , 19 ] in which it is mentioned that, through encapsulation, improved stability can be achieved in comparison to that of the extract alone, which is prone to a faster degradation. Evidence of the benefits of phytochemical encapsulation has also been found by using a bio-hybrid matrix consisting of Althaea officinalis L.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 1 µL culture from each test tube at MIC (with no visible growth) was inoculated using a loop (NuovaAptaca SRL, Canelli, Italy) on Columbia agar supplemented with 5% blood and maintained for 24 h at 37 °C for bacteria or on Sabouraud supplemented with chloramphenicol medium and maintained for 48 h at 28 °C for the yeast. The MBC/MFC was established as the lowest EO concentration, which killed 99.5% of the inoculated microorganisms [ 42 , 43 ]. All analyses were carried out in triplicate for each microbial strain.…”
Section: Methodsmentioning
confidence: 99%
“…S. enterica, Shigella flexneri serotype 2b, Enterococcus faecalis, E. coli, Pseudomonas aeruginosa, S. aureus, Streptococcus pneumoniae, Streptococcus pyogenes, Bacteroides fragilis, Candida albicans, Candida parapsilosis Antimicrobial activity [193] MCM-41 was also synthesized by the sol-gel method assisted by hydrothermal treatment and employing tetraethyl orthosilicate and n-cetyl-n,n,n-trimethyl ammonium bromide as silica source and template, respectively. Polyphenolic extracts of Salvia officinalis L. and Thymus serpyllum L. were encapsulated in these matrices and tested against S. enterica, S. flexneri serotype 2b, E. faecalis, E. coli, P. aeruginosa, S. aureus, S. pneumoniae, S. pyogenes, B. fragilis, C. albicans, and C.n parapsilosis, although showing milder improved antibacterial properties with respect to the parent extracts [193].…”
Section: Nanoparticles As Carriers Of Antimicrobial Natural Productsmentioning
confidence: 99%